Relativistic plasma nano-photonics for ultra-high energy density physics - Purvis, Michael Anthony, author; Rocca, Jorge J., advisor; Yalin, Azer P., committee member; Menoni, Carmen S., committee member; Marconi, Mario C., committee member (Colorado State University. Libraries, 2014)
The trapping of femtosecond laser pulses of relativistic intensity deep within ordered nanowire arrays is shown to volumetrically heat near solid density matter transforming it into ultra-hot highly ionized plasmas. The plasmas were generated by focusing intense ~ 60 femtosecond duration ultra-high-contrast laser pulses onto targets consisting of arrays of densely packed vertically aligned nanowires 35-80 nm diameter. X-ray spectra are presented showing that irradiation of Ni and Au nanowire arrays heats a plasma volume several µm in depth to reach extraordinarily high degrees of ionization (i.e. 26 times ionized Ni , 52 times ionized Au), in the process generating gigabar level pressures. Electron densities nearly 100 times greater than the typical critical density and multi-keV temperatures are achieved using laser pulses of only 0.5 J energy. The large plasma volume and high electron density lead to an increased hydrodynamic-to-radiative lifetime ratio that results in a significant increase in X-ray yield. Measurements from a filtered photodiode array reveal a 100X increase in emission with respect to polished flat targets for photons with energies greater than 9keV. Scaling to higher laser intensities promises to create plasmas with temperatures and pressures approaching those in the center of the sun.
Keywords: nanowire; laser; plasma; femtosecond; keV